Respuesta :
Answer:
[tex]y=(x-1)^2-7[/tex]
Step-by-step explanation:
Given : Equation = [tex]f(x)=x^2-2x-6[/tex]
To write in vertex form
Vertex form = [tex]y = a(x - h)^2+ k[/tex]
The given equation is in standard form [tex]y=x^2-2x-6[/tex]
to convert into vertex form we can use completing the square,
step 1 : [tex]y=x^2-2x-6[/tex]
step 2 : [tex]y+6=x^2-2x[/tex]
step 3 : [tex]y+6+1=x^2-2x+1[/tex]
step 4 : [tex]y+7=(x-1)^2[/tex]
step 5 : [tex]y=(x-1)^2-7[/tex]
It is a vertex form where a=1, h=1 , k=-7